Analisis Kualitas Isi dan Kalimat Efektif pada Teks Opini dalam Laman Website cnbcindonesia.com Edisi Januari 2025 sebagai Bahan Bacaan - Fitri Nur Hikmah; Ages Puspitasari; Izzatun Nihayah; Jihan Iffah Kamaliya; Aliyya Hidayati; Asep Purwo Yudi Utomo; Hera Septriana; Suntoro Suntoro (BADAN PENERBIT STIEPARI PRESS, 2025)
Writing is a productive activity that represents the writer's expression. However, in writing or composing sentences we cannot do it at will, one of which is in terms of effective sentences. The application of effective sentences can be found in opinion writing. Opinion texts are often the main source of information for readers in assessing an issue. In opinion text, the use of effective sentences is very important, so the message can be understood properly. Ineffective sentences can make the meaning ambiguous and unclear. Such ambiguity makes the quality of the opinion text decrease. As a result, the message to be conveyed does not reach the target. This study aims to identify, describe, and analyze the forms of language errors in the field of syntax, especially the use of effective sentences and content quality in opinion texts. The research methodology used is a methodological approach and a theoretical approach. The methodological approach that the author uses is descriptive qualitative, while the theoretical approach is syntactic. Data collection in this study was carried out through reading and recording techniques and purposive sampling techniques. The results of the analysis conducted with the object of opinion text on the January edition of the cnbn.indonesia.com website page, there are still many errors in the writing that cause sentences to be ineffective and make the quality of the opinion text content decrease. The benefit of this research is as a reference in writing, reading, improving, and analyzing the content of a text.